Role of Transition Zone Index in the Prediction of Clinical Benign Prostatic Hyperplasia - Güzelsoy, Muhammet; Kirkali, Ziya (Journal of urological surgery, 2016)
Objective The objective of this study was to determine the role of the transition zone (TZ) index (TZI) in the prediction of clinical benign prostatic hyperplasia (BPH) in patients who underwent transurethral prostatectomy (TUR-P) and to analyze the correlation between the amount of resected tissue and TZ volume (TZV). Materials and Methods Twenty-six male clinical BPH patients with obstructive complaints and 17 male benign prostate enlargement (BPE) patients without any complaints were included in the study. Both the groups were over the age of 50. Clinical BPH patients underwent complete TUR-P. Statistical analysis was done with SPSS. Sensitivity, specificity, positive and negative predictive values of TZI-as a method of assessing clinical BPH-were measured. Results There was a statistically significant difference in prostate volume, uroflowmetry patterns, prostate-specific antigen (PSA), International prostate symptom score (IPSS), TZV and TZI between the two groups. There was a correlation between TZV and the amount of resected tissue (r=0.97; p<0.0001). TZI also correlated with IPSS, quality of life (QL) and maximum flow rate (MFR) (r=0.58, p<0001; r=0.56, p<0.000; r=-0.70, p<0.0001, respectively). Conclusion TZI >0.40 has a high level of sensitivity and specificity in the prediction of clinical BPH among patients who undergo TUR-P due to obstructive symptoms and reported as BPH. There is a strong correlation between the amount of resected tissue and TZV. TZI is a valuable tool in diagnosis, and TZV gives valuable information about the patient to the surgeon. What's known on the subject? and What does the study add? Role of transition zone index in the prediction of clinical benign prostatic hyperplasia.